1989
DOI: 10.1007/bf01907977
|View full text |Cite
|
Sign up to set email alerts
|

Myosin P-light chain isoenzymes in the human heart: evidence for diphosphorylation of the atrial P-LC form

Abstract: We studied myosin light chains (LC) of human atrium and ventricle of normal and diseased individuals by a high-resolution 2-dimensional polyacrylamide gel electrophoresis (2D-PAGE) technique. Atrial LCs (ALC-1, ALC-2 (= P-LC)) revealed both higher molecular weights and lower isoelectric points (IEP) than their ventricular counterparts (VLC-1, VLC-2 (= P-LC)). Different P-LC forms with their distinct myosin isoenzymes have been designated as P-LC-polymorphism and myosin P-LC isoenzymes, respectively. In the dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Recent X-ray crystallographic analysis demonstrated that both essential and regulatory MLC are associated with the neck region of the myosin-S1 fragment (7). In the human heart, five different MLC isoforms exist which are expressed in a tissue-specific manner: there are three regulatory (phosphorylatable) myosin light chains, namely two ventricular-specific (VLC-2 and VLC-2*) and an atrial-specific (ALC-2) (8,9). The ventricular regulatory light chains are monophosphorlyated each, while the ALC-2 may be mono-and diphosphorylated (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent X-ray crystallographic analysis demonstrated that both essential and regulatory MLC are associated with the neck region of the myosin-S1 fragment (7). In the human heart, five different MLC isoforms exist which are expressed in a tissue-specific manner: there are three regulatory (phosphorylatable) myosin light chains, namely two ventricular-specific (VLC-2 and VLC-2*) and an atrial-specific (ALC-2) (8,9). The ventricular regulatory light chains are monophosphorlyated each, while the ALC-2 may be mono-and diphosphorylated (9).…”
Section: Introductionmentioning
confidence: 99%
“…In the human heart, five different MLC isoforms exist which are expressed in a tissue-specific manner: there are three regulatory (phosphorylatable) myosin light chains, namely two ventricular-specific (VLC-2 and VLC-2*) and an atrial-specific (ALC-2) (8,9). The ventricular regulatory light chains are monophosphorlyated each, while the ALC-2 may be mono-and diphosphorylated (9). Two essential myosin light chain isoforms are produced by two different genes, namely a VLC-1 which is the same isoform as the MLC-1s present in adult slow skeletal muscle, and an atrial-specific (ALC-1) isoform (10).…”
Section: Introductionmentioning
confidence: 99%
“…The ventricular myosin has two forms of regulatory light chains (VLC-2 and VLC-2*), both of which can be phosphorylated. The corresponding atrial light chain (ALC-2) can be both mono-and double-phosphorylated [Morano et al, 1989]. The relative phosphorylation levels were 25-30% for each light chain.…”
Section: Resultsmentioning
confidence: 99%
“…Atrium and Ventricle* Atrium Light chain ALC-2U ALC-2P ALC-2PP % 7 5 Ϯ 8 20 Ϯ 6 5 Ϯ 2 Ventricle Light chain VLC-2U VLC-2P VLC-2*U VLC-2*P % 8 7 Ϯ 5 13 Ϯ 5 86 Ϯ 6 14 Ϯ 6 *Separations were as described by Morano et al [1989]. For the atrium, the unphosphorylated (U), the phosphorylated (P) and the double-phosphorylated (PP) variants of the light chain 2 (ALC-2) were separated.…”
Section: Table I Relative Light Chain Phosphorylation In Myosin Extrmentioning
confidence: 99%
See 1 more Smart Citation